The Impact of Campus Residency on Retention of First-Generation African American College Students at Predominantly White Institutions - Goodwin, Pernell H.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2024)
The purpose of this study was to determine the impact of campus residency on the retention of first-generation, African American college student at PWIs. A sample of 20, full-time freshmen students participated in the study. The researchers used in-depth interviews to gain a deeper understanding of the impact campus residency is having on student retention. All information was self-reported by the participants. Limited research has been conducted on first-generation African American college students at Predominantly White Institutions. Study findings supported previous research in relation to on-campus housing and a sense of belonging. Study showed that campus residency had impacts on student’s retention as a result of their accessibility to academic support systems, extracurricular activities, importance of faculty and staff relationships, peer interactions, and a sense of belonging.